Fatores institucionais e o rendimento discente no exame de suficiência contábil - Santana, Aline Cordeiro (2023)
Obtaining professional registration to act as an accountant requires approval in the accounting sufficiency exam, but student failure rates have been noted in recent years. From 2011 to 2021, the average approval rate was just 30.80%. Accountant training takes place in Higher Education Institutions (HEI’s). Thus, it became important to analyze the factors that can influence institutions in the training of students and the consequent result in the accounting sufficiency exam. The Theory of the Educational Production Function (TEPF) considers institutional variables, students and professors as professionals to academic performance in academic tests. The research considered institutional factors, based on this theory, encompassing the period affected by the COVID-19 pandemic. Thus, the study aimed to identify the association between institutional factors and student approval rates in the sufficiency exam. As institutional variables, it was investigated the administrative category of the HEI, the type of academic organization, the region where the institution is located, and the allocation of workload for the contents required in the sufficiency exam. In the analysis of the pandemic period, it was analyzed whether there was a difference in the student results obtained before and during the pandemic, and in the exam carried out in an online format in 2020. It was conducted quantitative research, using statistical tests that allow verifying the relationship between the variables. The research sample consisted of 142 HEI’s. The results showed that public category HEIs, like universities, located in the South region, achieve better results in the accounting sufficiency exam. The worst results were obtained by private HEIs, such as Colleges and Higher Education Institutes, belonging to the North region. As for the disciplines, the contents of Public Sector Accounting, Accounting Theory, Accounting Audit, Accounting Expertise and Applied Portuguese Language are relevant to explain the student results in the relevant sufficiency exam. Observing the results obtained during the COVID-19 pandemic, it was found that there was an increase in the average percentage of approval in the edition carried out online. On the other hand, exams carried out in person during the COVID-19 pandemic had a statistically lower average of approval compared to other years. The research results contribute with the literature on accounting education in the country, to direct educational policies in economically less favored regions; for the teachers in the elaboration of the pedagogical curricula; and help the accounting students in the improvement to carry out the sufficiency exam and choice admission in HEI’s.